2018
DOI: 10.1111/cdev.13034
|View full text |Cite
|
Sign up to set email alerts
|

Children's Early Decontextualized Talk Predicts Academic Language Proficiency in Midadolescence

Abstract: This study examines whether children's decontextualized talk--talk about non-present events, explanations, or pretend-at 30 months predicts 7 th -grade academic language proficiency (age 12). Academic language (AL) refers to the language of school texts. AL proficiency has identified as an important predictor of adolescent text comprehension.Yet research on precursors to AL proficiency is scarce. Child decontextualized talk is known to be a predictor of early discourse development, but its relation to later la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 40 publications
3
60
0
3
Order By: Relevance
“…This finding indicates that children's home literacy environment may represent a common source of stable individual differences in vocabulary and grammatical development. This observation was not completely unexpected, as several longitudinal studies have demonstrated long‐lasting socioeconomic disparities in children's language skills (Hart & Risley, ; Huttenlocher, Waterfall, Vasilyeva, Vevea, & Hedges, ; Rowe, ; Uccelli, Demir‐Lira, Rowe, Levine, & Goldin‐Meadow, ). However, we were still somewhat surprised by the magnitude of the home literacy effects, considering that all of the predictors were very rough measures with a restricted range of scores in the sample and a nontrivial degree of missing data.…”
Section: Discussionmentioning
confidence: 65%
“…This finding indicates that children's home literacy environment may represent a common source of stable individual differences in vocabulary and grammatical development. This observation was not completely unexpected, as several longitudinal studies have demonstrated long‐lasting socioeconomic disparities in children's language skills (Hart & Risley, ; Huttenlocher, Waterfall, Vasilyeva, Vevea, & Hedges, ; Rowe, ; Uccelli, Demir‐Lira, Rowe, Levine, & Goldin‐Meadow, ). However, we were still somewhat surprised by the magnitude of the home literacy effects, considering that all of the predictors were very rough measures with a restricted range of scores in the sample and a nontrivial degree of missing data.…”
Section: Discussionmentioning
confidence: 65%
“…More research will be also essential to understand the relation between the cross‐disciplinary academic‐language skills tested here and learning in a particular discipline, such as science, history, or mathematics. Research on the precursors of academic language and on opportunities to learn S‐CALS in and outside of school throughout development also needs to be conducted (Uccelli, Demir, Rowe, Goldin‐Meadow, & Levine, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the literature shows that book-reading and oral story-telling have a positive effect on vocabulary development, not only in monolingual children (e.g., Mol & Bus, 2011;Uccelli et al, 2018), but also in bilingual children (Patterson, 2002;Scheele et al, 2010). The results on the effect of watching TV are mixed (Chonchaiya & Pruksananonda, 2008;Hudon et al, 2013).…”
Section: Book-readingmentioning
confidence: 97%
“…Katz (2001) found that parents' use of pretend utterances while playing with their three-year-olds related to children's receptive vocabulary and their skill at providing formal definitions in kindergarten. A recent study that focused on children's oral story-telling instead of parents' oral story-telling showed that children who produced a larger proportion of explanations, narratives, and pretend utterances at age 2;6 had significantly higher levels of academic language proficiency at the age of twelve (Uccelli, Demir-Lira, Rowe, Levine, & Goldin-Meadow, 2018). Not surprisingly, children's production of oral story-telling is very strongly associated with their parents' production of oral story-telling (Demir, Rowe, Heller, Goldin-Meadow, & Levine, 2015).…”
Section: Book-readingmentioning
confidence: 99%
See 1 more Smart Citation